The influence of facultative endosymbionts on honeydew carbohydrate and amino acid composition of the black bean aphid Aphis fabae. (9th December 2016) - Schillewaert, Sharon; Parmentier, Thomas; Vantaux, Amelie; Van den Ende, Wim; Vorburger, Christoph; Wenseleers, Tom
Abstract: The facultative endosymbionts Hamiltonella defensa and Regiella insecticola are commonly found in aphids. They are linked with various ecological benefits but generally occur at low prevalence, which indicates a possible harbouring cost. Little is known about how the presence of facultative endosymbionts is reflected in honeydew composition. Honeydew is the key mediator of the mutualism between aphids and their tending ants. The present study examines whether endosymbionts have an influence on aphid honeydew quality by comparing the amino acid and carbohydrate concentrations between infected and uninfected aphids. To this end, two genetic lines of the aphid Aphis fabae Scopoli are experimentally infected with different strains of Hamiltonella and Regiella . Infected aphids are shown to have reduced concentrations of amino acids in the honeydew compared with uninfected aphids. However, the presence of endosymbionts has no effect on the absolute amount of carbohydrates produced. Nevertheless, interclonal variation in honeydew composition between aphid genotypes is observed for both carbohydrate and amino acid production. These results imply that the nutritional value of honeydew depends on aphid genotype, as well as on the presence of secondary bacterial endosymbionts, which suggests that there is a physiological cost of harbouring endosymbionts and which could also impact aphid attractiveness to tending ants.